Bargaining and voting - Dan Usher (Queen's University, Department of Economics, 2010)
Government by majority rule voting requires that compromise be attainable, but not too easily. Little of the nation's business could be transacted without an ability on the part of the legislators and political parties to strike bargains, but government by majority rule voting could not withstand a bargaining equilibrium comparable to the general equilibrium in a competitive economy. Democratic government is designed to foster bargaining where it should be fostered and to impede bargaining where it should be impeded.
Keywords: C70; 330; Bargaining; Majority rule voting; Wahlverhalten; Wahlsystem; Verhandlungsmacht; Demokratie; Theorie